Educational Attainment in Afghanistan : An Economic Analysis - Auturupane, Harsha; Gunatilake, Ramani; Shojo, Mari; Ebenezer, Roshini (World Bank, Washington, DC, 2013)
Afghanistan's ability to enhance its human capital resources will determine the course of the nation's future economic, human and social development. Recognizing this, the Government of Afghanistan is committed to implementing policies aimed at getting children, particularly girls, into the education system. This paper aims to inform this process by investigating a variety of characteristics of children, such as their households, educational facilities, community factors, and spatial variables that are associated with education enrollment in urban and rural Afghanistan. This paper aims to investigate the factors underlying these low school enrollment figures and is structured as follows. Section one reviews previous research in this area. Section two provides a brief description the data and the methodology used in this analysis. In section three authors present the results which are then discussed in section four. In fact this study found that while the availability of appropriate schools is significantly correlated with primary and mid-school enrollment, they have a significant impact only on the enrollment of rural girls in high school. Right now, Afghanistan appears to be in a paradoxical situation: while education and better human capital needs to power economic growth, incomes need to expand to ease the constraints on education enrollment that are currently imposed by economic backwardness. To break out of this circle of constraints against enrollment, policy makers need to aggressively pursue policies that concentrate on easing the economic costs to households of children attending school, while enhancing the supply and quality of the facilities provided.